Chapter Nucleated Red Blood Cells Contribute to the Host Immune Response Against Pathogens - Nombela, Ivan (InTechOpen, 2019)
It has recently come to light that nucleated red blood cells (RBCs) of fish, amphibians, reptiles and birds are multifunctional cells, because in addition to being involved in gas exchange and transport, it has also been reported that they respond to pathogens by means of (i) phagocytosis, (ii) antigen presentation, (iii) production of cytokines and antimicrobial peptides, (iv) regulation of complement system, and (v) exerting paracrine molecular communication with other immune cells and modulating their functions. Similarly, human cord blood nucleated RBCs have been shown to exert a regulatory function in the innate immune response, by means of the suppression of the production of inflammatory cytokines. This chapter comprises the study of the implications of nucleated RBCs as mediators of both branches of immune system (innate and adaptive immune responses).